INDONESIA AND ASEAN IN 2025 - Yanyan Mochamad Yani; Ian Montratama (Universitas Jenderal Ahmad Yani, 2018)
This essay is motivated by an interest in a particular aspect of Indonesian foreign policy. Indonesia’s foreign policy has been called upon to serve the goals of national development. The national development takes place within a regional and global environment. Indonesia’s most immediate environment is the sub-region of Southeast Asia, and for that reason the Association of Southeast Asian Nations (ASEAN), which remains the cornerstone of Indonesian foreign policy. ASEAN Community is a continuing process. It will continue to promote the expansion and then deepening of the implementation of ASEAN Community Blueprints beyond 2015. ASEAN Community Vision 2025 was approved and signed at ASEAN Summit Meeting, 21 – 22 November 2015 in Kualalumpur, Malaysia. In the mean time for Indonesia itself, there are some impediments in the implementation of Indonesia’s maritime nexus will continue to hedge against the ASEAN Economic Community as well as the major powers interests, especially with RCEP (Regional Comprehensive Economic Partnership led by ASEAN but heavily influence by China and the Trans Pacific Partnership that once led by the United States of America and seems abandon in Donald Trump era. The study reveals that he strategic implication of the above possible development appeals the need of new approaches to Indonesia. Some basic assumptions can be derived from the foregoing examination of Indonesian foreign policy concepts, a changing Asian strategic environment, and uncertainties of interdependence. It may be reasonable to assume that Indonesia has the capability to increasingly strengthen linkages among defense, security, and foreign policy aspects which leads to an adequate Indonesian national security policy.